“Recursos innovadores para el aprendizaje del área de ciencias sociales.” - Galeas Carpio, Erika Lisbeth (2022)
The constant changes in science and technology have generated great impact in different areas, one of them is education, which must respond and adjust to the demands of today's world in which individuals can adapt to it. In this sense, the use of information and communication technology takes on great importance because it presents a diversity of tools that can be applied in the pedagogical process, which will allow creating a collaborative learning space in which students and teachers interact in an interactive and participatory way. However, the use and application in technological learning environments are little used due to different socio-educational aspects that limit the introduction of digital media in teaching and learning, in such a way that the use of the book is maintained as the only source of support in the pedagogical process that is why there is a need to create technological didactic recursion that contributes to generating learning for life. In this virtue, the objective of the present project is to create technological resources that contribute to the improvement in the learning in the area of social sciences of the students of the fourth year of basic education of the Educational Unit "Dr. Trajano Naranjo Iturralde”. The methodology of this project was based on qualitative research because it allowed us to reflect about the didactic resources in the context of educational practice, the method applied is the inductive, as well as the observation technique, and its instrument the observation guide, that allowed us to collect information on the technological and non-technological didactic resources used during the teaching-learning process. As a result, digital didactic recursion was obtained, elaborated in tools such as Animaker, World Wall, PowerPoint, Mobbyt, Camba, and Educaplay with topics extracted from the social studies book from fourth grade of basic general education, the same ones used by teachers and students. This research contributes to the development of digital skills, to the increase of recursion and teaching strategies, in the same way, the constant motivation of the student is encouraged during the teaching-learning process.